Changer de métier pour devenir enseignant : transitions professionnelles et dynamiques identitaires - Thérèse Perez-Roux (Recherches en Éducation)
In France entering a teaching job is associated with a period of sandwich training. The study deals with this moment of professional transition for future teachers in professional high schools who have to assure the training of pupils in a profession they themselves practised for several years. On the basis of a double methodology we present three portraits of future teachers in road driving. People with different experience concerning the level of diplomas, the professional experience the relation to training and to job(s). The results give an account of the registers of mobilized knowledge: working as obstacles or resources in the process of professionalization. They enlighten certain conditions facilitating the professional transition: complementarity of training spaces, modalities of insertion in the school, support on the work collectives, temporality necessary to the transformation. Form of rehandling appear in a differenciated way. They are organised around an identity project which requires to connect past and future, an image of oneself and recognition of others; diversity of the experiences and consistency of action in a new professional universe for which many landmarks remain to build.